Assessment of Some Strength Properties of Certain Clones Eucalyptus tereticornis SM. from Sarapakka, Andhra Pradesh - Kothiyal, V.; Sudheendra, R.; Rao, R. V. (Indian Forester, 2006)
Specific gravity and some of the mechanical prperties of five clones of Eucalyptus tereticornis Sm. developed by ITC Bhadrachalam are reported in this paper. The five clones represented by four trees each of four and half years of age studied are from Sarapakka (Andhra Pradesh) grown on red soil. The results were compared with values reported for the same clones of even age group from Cherupally (Andhra Pradesh) demonstration plot grown on black soil. Clone number 4 had overall better mechanical properties having highest value for all the properties; followed by clone 6.